Hygroscopic effects on the mobility and mass of cigarette smoke particles. (August 2015) - Johnson, Tyler J.; Olfert, Jason S.; Yurteri, Caner U.; Cabot, Ross; McAughey, John
Abstract: The hygroscopic growth of particles, produced from a University of Kentucky 3R4F reference cigarette smoked following Health Canada Intense (HCI) puffing parameters (55 mL puff of 2 s duration, every 30 s), was measured in terms of the electrical mobility diameter and particle mass, using a Hygroscopic Tandem Differential Mobility Analyzer (HTDMA) and Centrifugal Particle Mass Analyzer (CPMA) system. Both the particle mobility diameter and mass growth factors were found to agree with previously determined values and hygroscopicity models. The mobility diameter growth factor of the particles produced from either a University of Kentucky 3R4F or 1R5F reference cigarette, following HCI puffing parameters, were found to be very similar. As the relative humidity (RH) approached saturation, the effects of the initial particle size on the mobility growth factor became more dominant, with larger particles growing proportionally larger than smaller particles. From the measured mobility diameter and mass growth factors, the density growth factor was calculated. This parameter showed that the particle density increased as the sample relative humidity increased. This case is only possible, given that the dried smoke particle density (1109±118 kg/m 3 ) was determined to be greater than the density of water, if the water condensation on the smoke particle dissolves at least a portion of it, resulting in a significant increase in mass with only a small increase volume. Highlights: The maximum mobility growth factor measured was 1.27 at 96% RH. The maximum mass growth factor measured was 1.53 at 93.7% RH. Particle size had a small effect on growth, that increased as RH increased. As RH increased, particle mass grew at a faster rate than particle volume. At least a portion of the particle composition was water soluble.